2006
DOI: 10.1177/0269881106059733
|View full text |Cite
|
Sign up to set email alerts
|

Intensity dependence of auditory evoked dipole source activity in polydrug ecstasy users: evidence from an 18 months longitudinal study

Abstract: Numerous animal studies have been able to demonstrate neurotoxic damage to central serotonergic systems after exposure to 3,4-methylenedioxymethamphetamine (MDMA, ecstasy). It has been suggested that a high loudness dependence of auditory evoked potentials (LDAEP) and, particularly, of the tangential N1/P2 source activity is associated with a low functioning of serotonergic activity. Therefore, the LDAEP may be used as a non-invasive indicator for a possible neurotoxic damage caused by the long-term use of ecs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Guille and colleagues had compared drug effects on both methods (with no significant differences reported) but did not perform a baseline comparison between the single‐electrode method and DSA (Guille et al , ). However, a large number of studies using either the single‐electrode method (e.g., Kawohl et al , , ; O'Neill et al , , ; Roser et al , ); Oliva et al , or DSA (e.g., Juckel et al , ; Daumann et al , ; Juckel et al , ) exists. We therefore suggest to continue with multichannel measurements in the future and to perform both single‐electrode estimations and DSA in order to be able to relate the results to the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Guille and colleagues had compared drug effects on both methods (with no significant differences reported) but did not perform a baseline comparison between the single‐electrode method and DSA (Guille et al , ). However, a large number of studies using either the single‐electrode method (e.g., Kawohl et al , , ; O'Neill et al , , ; Roser et al , ); Oliva et al , or DSA (e.g., Juckel et al , ; Daumann et al , ; Juckel et al , ) exists. We therefore suggest to continue with multichannel measurements in the future and to perform both single‐electrode estimations and DSA in order to be able to relate the results to the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results could not be duplicated by other research groups (Daumann et al 2006;Guille et al 2008;Juckel et al 2007;O'Neill et al 2008a;Roser et al 2009). According to the review by O'Neill et al (2008a), the LDAEP shows more promise as a potential predictor of antidepressant treatment responses Lee et al 2005;Linka et al 2005;Mulert et al 2007;Pogarell et al 2007a), although the acute depletion studies in humans that provide little evidence of LDAEP is sensitive to the acute changes in 5-HT function (Debener et al 2002;Norra et al 2008;O'Neill et al 2008b).…”
Section: Introductionmentioning
confidence: 89%
“…Abstinent users of "ecstasy" (methylenedioxymethamphetamine), a drug shown to have neurotoxic effects on central serotoninergic systems in animal research, also show increased intensity dependence compared with control subjects [27][28]. An 18-month follow-up study also found that prior ecstasy use was associated with increased intensity dependence [29]. However, changes in ecstasy use at follow-up were not related to changes in intensity dependence, leading the researchers to speculate whether the increased intensity dependence exhibited by ecstasy users represents a preexisting trait or is an irreversible change in 5-HT function.…”
Section: Introductionmentioning
confidence: 99%